On the attribution of authorship for several elasmobranch species in Müller and Henle’s Systematische Beschreibung der Plagiostomen (Chondrichthyes, Elasmobranchii) - Jones, Christian M.; Driggers, William B. Iii; Castro, José I.; Carvalho, Marcelo R. De (Zootaxa, 2015)
Even in light of the recent peak in new species descriptions of elasmobranchs (summarized in White & Last, 2012), Johannes Müller and Friedrich Henle’s Systematische Beschreibung der Plagiostomen (1839–1841) stands as a major achievement in chondrichthyan taxonomy. This volume included all elasmobranch species then known as well as descriptions of 61 new species (for a total of 214 species), and established many of the family-level groups still in use today. Müller & Henle’s work, however, would not have been possible without the collaboration of other naturalists who provided specimens for examination, detailed notes, and illustrations (Müller & Henle, 1841). Four men in particular made significant enough contributions to warrant Müller & Henle attributing the authority of several species to them: Achille Valenciennes (1794–1865), Gabriel Bibron (1805–1848), Heinrich Bürger (1806–1858), and Andrew Smith (1797–1872). In nearly every case however, authority is currently placed on Müller & Henle themselves, and not the gentlemen to whom they gave credit.